The Significance of SKABAPUTRA in the Socio-cultural Space of the Lithuanian-Latvian Borderland - Auksė Noreikaitė (Acta Humanitarica Academiae Saulensis)
The aim of the article is to investigate the significance of the traditional Latvian dish – skabaputra (Latvian skābputra – sour porridge made from barley groats and curdled milk) – in the socio-cultural space of the Lithuanian-Latvian borderland in various periods. The research is based on the empirical material collected by the author in several stages (between 2008 and 2019) in the municipalities of Lithuanian-Latvian borderland. The methods applied in this research were quantitative content analysis, case analysis, interpretative, and comparative methods.